POTENSI RUMPUT LAUT SEBAGAI BAHAN DASR KOSMESEUTIKAL - Rahmadi, Puji; Pangestuti, Ratih; Salim, Gazali (Jurnal Harpodon Borneo, 2011)
Nowadays we were facing to the global warming which is causing climate changes. Global warming also promote by environmental degradation. Increment of human population and development on industrial realm are the main cause of environmental degradation. Wetland is one of environmental bufferwhich could enhance the environmental stress. Doing the wetland restoration is an effort to enhance ecological degradation. In this paper were discusses about wetland definition, functions, wetland restoration, effect of restoration and also some study cases of wetland restoration published by some researcher. Tidal Wetland Restoration itself could be defined as an actions taken in a converted or degraded natural wetland that result in the reestablishment of ecological processes, functions, and biotic/abiotic linkages and lead to a persistent, resilient system integrated within its landscape (Lewis, 1989). It must expect restoration could bring the better effluence to the ecology, however some time it?s not just happen like ideally. Some of the restoration activity could promote and lead the ecological degradation in the neighbor habitat from which restoration activity was conducted. Therefore to enhance the sustainability, restoration and good management should be applied in order and in good monitoring. Keywords : wetland, ecological, restoration, sustainability.